The first report of the ante-mortem diagnosis of Ollulanus tricuspis infection in two dogs - KATO, Daiki; OISHI, Mariko; OHNO, Koichi; NAKASHIMA, Ko; WADA, Atsuhito; FUKUMOTO, Shin-ichiro; MORITA, Tatsushi; IMAI, Soichi; TSUBOI, Masaya; CHAMBERS, James K.; UCHIDA, Kazuyuki; TSUJIMOTO, Hajime (Journal of Veterinary Medical Science, 2017)
NOTE Internal Medicine The first report of the ante-mortem diagnosis of Ollulanus tricuspis infection in two dogs KATO, Daiki1), OISHI, Mariko1), OHNO, Koichi1)*, NAKASHIMA, Ko1), WADA, Atsuhito1), MORITA, Tatsushi2), IMAI, Soichi2), TSUBOI, Masaya3), CHAMBERS, James K.3), UCHIDA, Kazuyuki3) and TSUJIMOTO, Hajime1) 1)Department of Veterinary Internal Medicine, Graduate School of Agricultural and Life Sciences, The University of Tokyo, 1–1–1 Yayoi, Bunkyo-ku, Tokyo 113–8657, Japan 2)Division of Veterinary Infectious Disease, Department of Veterinary Pathobiology, Nippon Veterinary and Life Science University, 1–7–1 Kyonanchyo Musashino, Tokyo 180–8602, Japan 3)Department of Veterinary Pathology, Graduate School of Agricultural Should have been NOTE Internal Medicine The first report of the ante-mortem diagnosis of Ollulanus tricuspis infection in two dogs KATO, Daiki1), OISHI, Mariko1), OHNO, Koichi1)*, NAKASHIMA, Ko1), WADA, Atsuhito1), FUKUMOTO, Shin-ichiro2), MORITA, Tatsushi3), IMAI, Soichi3), TSUBOI, Masaya4), CHAMBERS, James K.4), UCHIDA, Kazuyuki4) and TSUJIMOTO, Hajime1) 1),Department of Veterinary Internal Medicine, Graduate School of Agricultural and Life Sciences, The University of Tokyo, 1–1–1 Yayoi, Bunkyo-ku, Tokyo 113–8657, Japan 2)Laboratory of Veterinary Parasitology, Department of Pathobiology, School of Veterinary Medicine, Rakuno Gakuen University, Ebetsu, Hokkaido 069-8501, Japan 3)Division of Veterinary Infectious Disease, Department of Veterinary Pathobiology, Nippon Veterinary and Life Science University, 1–7–1 Kyonanchyo Musashino, Tokyo 180–8602, Japan 4)Department of Veterinary Pathology, Graduate School of Agricultural